Introduction to unmanned aerial vehicles - Garg, Pradeep K. (New Age Reference, an imprint of New Age Internationa (P) Limited, Publishers, 2021)
"Drones/Unmanned Aerial Vehicles (UAVs) are aerial devices that can fly with a human remotely controlling them, or fly autonomously without any human intervention. The increasingly use of drones/UAVs has created a rapid evolution of payload hardware and software, multispectral, thermal and hyperspectral sensors, and environmental sensors. However, before UAVs can be used for such real-world applications, it is necessary to understand the types of drones/UAVs, their components, sensors employed, operational methods and software needed to analyse the data and application requirements. The book is divided into eight chapters to take the reader from the foundations of UAV to active research topics in this fast developing arena. Each chapter is written in a simple language with several illustrations and tabular data to provide better understanding of the topic. Since the technology is gaining popularity world-wide, the students will find the book very useful to update their knowledge for UAV based data collection approaches. The main key feature of this book is that it concisely covers the principles of UAV, UAV types and missions, hardware and software components employed in UAV, data collection methods, UAV regulatory system, applications in various fields and future research areas. The structure and character of images, and spatial & point cloud data datasets are crucial to understand their effective analysis in various applications, and develop innovative approaches. The book covers the course contents requirement of UG (civil engineering) and PG (geoinformatics) as well as computer science, mechanical engineering, electronics and communication engineering, information technology, geography, environmental science, earth science, students and research scholars, and those who have curiosity to learn about drone/UAV. Since UAV is a multidisciplinary tool having applications in civil engineering, resources management, disaster & rescue service, oil & gas monitoring, forestry, agriculture, good delivery, health system, crowd management, traffic regulation, media & journalism, urban planning, infrastructure monitoring, 3D mapping, surveillance, search & rescue, businesses etc., so the book also intends to be very useful for those who are working in UAV-based application areas."--